A Performance Investigation on IoT Enabled Intra-Vehicular Wireless Sensor Networks - Rahman, Md. Arafatur; Ali, Jahan; M. Nomani, Kabir; Azad, Saiful (Universiti Malaysia Pahang, 2017)
The concept of Internet of Things (IoT) can be utilised in vehicles, since the number of sensor nodes in vehicles is rising tremendously because of the uplifting demand of applications for security, safety and convenience. In order to establish the communication among these nodes inside a vehicle, a controller area network with wired architecture provides a prominent solution. However, this solution is not flexible because of the architectural complexity and the demand for a large number of sensors inside the vehicle; hence wired architectures are replaced by wireless ones. Moreover, scalability will be an important issue while introducing the IoT concept in Intra-Vehicular Wireless Sensor Networks (IVWSNs). In this paper, a comprehensive performance investigation on the IoT enabled IVWSNs (IoT-IVWSNs) to be carried out in order to address this issue. The overview of the IoT-IVWSNs with a comparative study of the existing technologies and the design challenges for such network are provided. The link design between an end-device and the control unit is analysed, and the performance of the network has been investigated and some open research issues are addressed. It reveals that the delay in packet transmission increases due to higher traffic loads and the number of end-devices. This result demonstrates that the existing MAC protocol works well for a small network (i.e., a network with a maximum number of 50 nodes) but is not suitable for a large network (i.e., a network with more than 50 nodes). The outcome of this research helps to design a smart car system.